Robust Thyroid Gene Expression and Radioiodine Uptake Induced by Simultaneous Suppression of BRAF V600E and Histone Deacetylase in Thyroid Cancer Cells - Cheng, Weiwei (J Clin Endocrinol Metab, 2016)
CONTEXT: Use of BRAF V600E inhibitors to restore thyroid iodide-handling gene expression and radioactive iodine (RAI) avidity is an attractive therapeutic strategy for RAI-refractory thyroid cancer, but recent initial clinical responses were modest. Given histone deacetylation at the sodium/iodide symporter promoter by histone deacetylase (HDAC) as a mechanism, simultaneously targeting BRAF V600E and HDAC could be a more effective strategy. OBJECTIVES: The objective of the study was to test whether suppressing both BRAF V600E and HDAC could more effectively induce thyroid gene expression and RAI uptake in thyroid cancer cells. RESEARCH DESIGN: We tested the BRAF V600E inhibitor PLX4032 (vemurafenib) and the HDAC inhibitor SAHA (vorinostat), two major anticancer drugs currently approved for clinical use, in inducing thyroid gene expression and RAI uptake in thyroid cancer cells. RESULTS: PLX4032 alone induced a modest expression of thyroid genes and RAI uptake preferentially in thyroid cancer cells harboring BRAF V600E. SAHA showed an effect in a genetic-independent manner in all the cells. A robust synergistic effect on thyroid gene expression and RAI uptake was observed in BRAF V600E-positive thyroid cancer cells when the two inhibitors were simultaneously used. This was dramatically enhanced further by TSH; triple combination of PLX4032, SAHA, and TSH showed the most robust effect on thyroid gene expression and RAI uptake in cells harboring BRAF V600E. Abundant sodium/iodide symporter protein expression in thyroid cancer cells under these conditions was confirmed by immunofluorescent microscopy. CONCLUSIONS: Simultaneously suppressing BRAF V600E and HDAC, particularly when cotreated with TSH, induced a far more robust expression of thyroid genes and RAI uptake in thyroid cancer cells than suppressing BRAF V600E alone. Triple combination of PLX4032, SAHA, and TSH is a specific robust regimen to restore RAI avidity in RAI-refractory BRAF V600E-positive thyroid cancer, which warrants clinical trials to confirm.